A Peptoid Ribbon Secondary Structure1. Issue 19 (9th April 2013) - Crapster, J. Aaron; Guzei, Ilia A.; Blackwell, Helen E.
<x xml:space="preserve">Abstract</x> Joining the fold: A series of peptoids, or oligomers of N‐substituted glycines, adopt a novel secondary structure, designated the "peptoid ribbon". This fold was stable at short chain lengths and in a variety of solvents (both organic and aqueous), and arose from a primary sequence of peptoid monomers designed to enforce an alternating pattern of cis and trans main‐chain amides.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>